2008
DOI: 10.1007/bf03345602
|View full text |Cite
|
Sign up to set email alerts
|

The biological characterization of neuroendocrine tumors: The role of neuroendocrine markers

Abstract: Neuroendocrine tumors (NET) may originate in different organs, from cells embryologically different but expressing common phenotypic characteristics, such as: the immuno-reactivity for markers of neuroendocrine differentiation (defined as "pan-neuroendocrine"), the capacity to secrete specific or aspecific peptide and hormones and the expression of some receptors, that are at the basis of the current diagnostic and therapeutical approach, peculiar to these tumors. NET have been conventionally distinguished in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 36 publications
1
43
0
5
Order By: Relevance
“…Actually, the definition of NENs gathers a heterogeneous group of diseases, including malignancies from several anatomic areas, such as stomach, intestine, rectum, pancreas, lung, adrenals and thyroid, and with variable evolution, from indolent to rapidly progressive (Baudin 2007, Yao et al 2008a. The feature joining these tumors is that they arise from specialized cells spread throughout the body, belonging to the so-called diffuse neuroendocrine system, whose main ability is to produce, store and release the bloodstream bioactive molecules (Langley 1994, Kaltsas et al 2004, Ferolla et al 2008. Whether this biological activity produces characteristic syndromes represents the major factor affecting clinical scenario of NENs, which are accordingly classified into functional and nonfunctional (Kulke et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the definition of NENs gathers a heterogeneous group of diseases, including malignancies from several anatomic areas, such as stomach, intestine, rectum, pancreas, lung, adrenals and thyroid, and with variable evolution, from indolent to rapidly progressive (Baudin 2007, Yao et al 2008a. The feature joining these tumors is that they arise from specialized cells spread throughout the body, belonging to the so-called diffuse neuroendocrine system, whose main ability is to produce, store and release the bloodstream bioactive molecules (Langley 1994, Kaltsas et al 2004, Ferolla et al 2008. Whether this biological activity produces characteristic syndromes represents the major factor affecting clinical scenario of NENs, which are accordingly classified into functional and nonfunctional (Kulke et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, researchers aimed to identify markers useful for (a) diagnosis anticipation and refining, (b) prognostic stratification and (c) disease evolution monitoring and response to treatment. Based on the relationship with codified hormone-related syndromes, circulating markers of NEN are differentiated in common or broad spectrum, including chromogranin A (CgA), pancreatic polypeptide and neuron-specific enolase, and specific or individual, including serotonin and its metabolite 5-hydroxyindolylacetic acid, gastrin, glucagon, insulin, C-peptide, vasoactive intestinal peptide, somatostatin, histamine, calcitonin, parathyroid, somatotropic, adrenocorticotropic hormones, catecholamines and their metabolites and neuropeptides (Ferolla et al 2008). The present review is focused on CgA, a hydrophilic glycoprotein abundantly expressed in large dense core vesicles of neuroendocrine cells, whose main biological role is to regulate calcium-mediated exocytosis (Borges et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that NETs can develop in almost all tissues or organs in the body, especially in the gastroenteropancreatic tract and lungs and rarely in the ovary [2]. They are characterized by an ample range of histological appearance and biological behavior These tumors show tissue immunoreactivity for markers of neuroendocrine differentiation (synaptophysin, chromogranin A, CD56, and NSE) and may secrete various peptides and hormones [4]. NETs are frequently placed in the submucosa or more deeply intramurally and can invade surrounding tissues.…”
Section: Biologymentioning
confidence: 99%
“…Increased concentrations of circulating chromogranin A (CgA) are characteristic of neuroendocrine tumors (NETs), although the diagnostic and prognostic usefulness of this marker is widely debated (1,2). Some studies reported low sensitivity and specificity of CgA concentrations for the diagnosis of NET.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported low sensitivity and specificity of CgA concentrations for the diagnosis of NET. Concentrations may be dependent on tumor features, such as: type, secretory activity, neuroendocrine differentiation degree and total burden (1,2). However, several lines of evidence show that the diagnostic accuracy is affected primarily by the type of assay used to measure CgA (1,(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%